Separation membrane and method for manufacturing separation membrane
By using a direct coating method with nanomaterials and organosilica having a silsesquioxane structure on a porous support, the separation membrane achieves high permeability and selectivity, addressing the limitations of existing technologies.
Patent Information
- Application Number
- JP2021089219
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-05-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-05-27
AI Technical Summary
Existing separation membranes face challenges in achieving high permeability and selectivity due to difficulties in controlling the chemical structure of silicone-based functional polymer layers and the increased permeability resistance caused by intermediate layers.
A separation membrane is developed with a porous support coated directly with a separation layer comprising nanomaterials such as cellulose nanofibers or graphene oxide, and organosilica with a silsesquioxane structure, allowing for controlled pore size and improved selectivity.
The approach results in a separation membrane with enhanced permeability and selectivity, enabling more efficient separation treatments such as water treatment, while simplifying the film forming process.
Smart Images

Figure 0007662187000002 
Figure 0007662187000003 
Figure 0007662187000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a separation membrane and a method for producing the separation membrane. [Background technology]
[0002] Conventionally, membrane separation has been used as a method for separating target substances with low energy. Membrane separation is used in various industrial fields including water treatment. The separation characteristics of the separation membrane used in membrane separation are affected by the pore size, surface characteristics, membrane structure, etc. of the separation membrane. Separation membranes made of silicon-based materials with amorphous structures are commonly used, and silicon-based oxides such as silica (SiO2) and silsesquioxane ((RSiO 1.5 ) n ), silicone ((R2SiO) n Various separation membranes using these as the separation membrane material have been developed (for example, Patent Document 1). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2016 / 136294 Summary of the Invention [Problem to be solved by the invention]
[0004] In Patent Document 1, silicone ((RSiO) n ), a functional polymer layer composed of a siloxane compound having a polydimethylsiloxane structure is formed on the upper or lower layer of the separation layer to make the separation layer thinner. Specifically, the separation membrane of Patent Document 1 has a functional polymer layer formed on the upper layer of the separation membrane to increase the mechanical strength, thereby making the separation layer thinner and improving the permeability of the separation membrane. Another separation membrane of Patent Document 1 has a functional polymer layer formed on the lower layer of the separation layer, i.e., as an intermediate layer between the separation layer and the porous layer, and the porous surface is smoothed to make the separation layer thinner and improve the permeability of the separation membrane.
[0005] However, the silicone ((RSiO) n ) is difficult to control the chemical structure, so it is difficult to adjust the pore size and improve the selectivity. In addition, since a functional polymer layer is formed as an intermediate layer, the permeation resistance of the intermediate layer increases the permeation resistance of the separation membrane, hindering the improvement of the permeability of the separation membrane.
[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a separation membrane having high permeability and selectivity, and a method for producing the separation membrane. [Means for solving the problem]
[0007] In order to achieve the above object, a separation membrane according to a first aspect of the present invention comprises: The pore size is 30 nm or more and 5 μm or less. A porous support; A separation layer formed on the porous support and including a nanomaterial and an organosilica having a silsesquioxane structure. 、 The nanomaterial comprises: The nanofibers are cellulose nanofibers having a fiber diameter of 1 nm or more and less than 100 nm, or graphene oxide having a thickness of 1 nm or more and less than 10 nm and a sheet length of 100 nm or more.
[0008] The porous support is selected from the group consisting of cellulose ester, cellulose, polyacrylonitrile, polytetrafluoroethylene, polymethylpentene, and polysulfone. This may also be the case.
[0010] The organosilica is produced using alkoxysilane as a precursor. This may also be the case.
[0011] A method for producing a separation membrane according to a second aspect of the present invention comprises the steps of: A preparation step of preparing a coating sol containing a nanomaterial and an organosilica having a silsesquioxane structure; The coating sol , the pore size is 30 nm or more and 5 μm or less A coating step of coating a porous support; a film-forming step of forming a film by filtering the coating sol applied in the coating step under reduced pressure or pressure; A heat treatment process for forming a separation layer by heat-treating the coating sol formed in the film-forming process. fruit, The nanomaterial comprises: The nanofibers are cellulose nanofibers having a fiber diameter of 1 nm or more and less than 100 nm, or graphene oxide having a thickness of 1 nm or more and less than 10 nm and a sheet length of 100 nm or more.
[0013] The organosilica is produced using alkoxysilane as a precursor. This may also be the case.
[0014] The porous support is selected from the group consisting of cellulose ester, cellulose, polyacrylonitrile, polytetrafluoroethylene, polymethylpentene, and polysulfone. This may also be the case. Effect of the Invention
[0015] According to the separation membrane and the method for producing the separation membrane of the present invention, the nanomaterial contained in the separation layer makes it possible to directly coat the separation layer on the porous support, thereby reducing the permeation resistance of the separation membrane and improving the permeability. In addition, the organosilica having a silsesquioxane structure contained in the separation layer makes it possible to control the chemical structure of the separation layer and adjust the pore size, thereby improving the selectivity. [Brief description of the drawings]
[0016] [Figure 1] 1 is a schematic cross-sectional view of a separation membrane according to an embodiment of the present invention. [Diagram 2] FIG. 1 is a schematic cross-sectional view of a conventional separation membrane having an intermediate layer. [Diagram 3] 2 is a flowchart showing the flow of a method for producing a separation membrane according to an embodiment. [Figure 4] 1 is a graph showing the results of thermogravimetry of a cellulose nanofiber sol. [Diagram 5]1 is a graph showing the results of structural analysis of cellulose nanofiber sol by Fourier transform infrared spectroscopy. [Figure 6] 1 is a graph showing the relationship between the film thickness and characteristics of a separation layer using cellulose nanofibers, where (a) is a graph showing the separation coefficient, and (b) is a graph showing the water vapor permeability and the nitrogen permeability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] A separation membrane 10 according to the present embodiment will be described. As shown in Fig. 1, separation membrane 10 according to the present embodiment comprises separation layer 11 and support 12. As shown in Fig. 2, a conventional separation membrane 20 having a multilayer structure with an intermediate layer comprises separation layer 21, intermediate layer 22, and support 23. In order to reduce the permeation resistance and increase the permeability of the separation membrane, separation membrane 10 according to the present embodiment does not form an intermediate layer that increases the permeation resistance, but forms separation layer 11 by directly coating sol on support 12.
[0018] (Support) The separation membrane 10 includes a support 12 (porous support) made of a porous substrate to increase the mechanical strength of the separation membrane 10. The porous substrate is not particularly limited, but examples thereof include cellulose ester, cellulose (filter paper), polyacrylonitrile, fluororesins such as polytetrafluoroethylene, polymethylpentene, polysulfone, and the like.
[0019] (separation layer) The separation layer 11 is formed on the support 12, and separates a target substance by using pores that allow the passage of a specific substance. The separation layer 11 is made of a nanomaterial and a silsesquioxane structure ((RSiO 1.5 ) n The nanomaterial is not particularly limited as long as it can be directly coated on the porous support. Examples of the nanomaterial include cellulose nanofiber (CNF) and graphene oxide.
[0020] Since the nanomaterial according to the present embodiment has a high aspect ratio, it is possible to form a thin film by directly coating the nanomaterial on the support 12. For example, CNF can have a diameter of about several nm to several tens of nm and a length of about several hundreds of nm, and graphene oxide can have a thickness of about several nm and a sheet size of about several hundreds of nm. By directly coating the support 12 with these nanomaterials with high aspect ratios, it is possible to form a thin film.
[0021] In addition, organosilica having a silsesquioxane structure is produced using an alkoxysilane as a precursor. Examples of the alkoxysilane include crosslinked alkoxysilanes such as 1,2-bis(triethoxysilyl)ethane (BTESE), 1,2-bis(triethoxysilyl)methane (BTESM), 1,2-bis(triethoxysilyl)propane (BTESP), 1,4-bis(triethoxysilyl)benzene (BTESB), and bis[3-(trimethoxysilyl)propyl]amine (BTPA); and side chain alkoxysilanes such as methyltriethoxysilane and 3-aminopropyltrimethoxysilane.
[0022] The above-mentioned nanomaterials such as CNF and graphene oxide have many hydroxyl groups and are covalently bonded to alkoxysilane, which is a precursor of organosilica. As a result, an organosilica layer grows from the surface of the CNF, graphene oxide, etc. In this embodiment, a composite sol of the nanomaterial and organosilica is produced, and this composite sol is applied to the support 12 as a coating sol to form a thin film separation layer 11. A detailed film formation method will be described later.
[0023] (Membrane manufacturing method) Hereinafter, the separation membrane manufacturing method according to the present embodiment will be described with reference to the flowchart in Fig. 3. The manufacturing method of separation membrane 10 according to the present embodiment includes a preparation step of preparing a coating sol, a coating step of applying the coating sol to support 12, a membrane formation step of forming a membrane by filtration under reduced pressure or pressure of the applied coating sol, and a heat treatment step of heat treating a separation membrane material to form separation layer 11.
[0024] In the separation membrane manufacturing method according to the present embodiment, first, in a preparation step, a coating sol to be applied onto the support 12 is prepared. The coating sol contains organosilica having a silsesquioxane structure and a nanomaterial. The coating sol according to the present embodiment is produced by mixing a BTESE sol and a cellulose nanofiber sol (hereinafter also referred to as a CNF sol).
[0025] First, a BTESE sol is prepared (step S11). Specifically, BTESE and ethanol are mixed, and water is added dropwise while stirring at room temperature, and then hydrochloric acid diluted with ethanol is further added dropwise. Then, the mixture is stirred in a water bath at 50°C for 1 hour to prepare a BTESE-acid sol.
[0026] In addition, a CNF sol is prepared (step S12). Specifically, CNF and water are mixed and ultrasonically dispersed at 28 kHz for 5 minutes to prepare a CNF sol. For example, a CNF M sol (manufactured by Sugino Machine Co., Ltd., concentration 2 wt%, fiber diameter 10 to 50 nm, degree of polymerization 650) can be used as the CNF sol.
[0027] The above BTESE sol and CNF sol are mixed to prepare a coating sol (step S13). Specifically, the BTESE sol prepared in step S11 is added to the CNF sol prepared in step S12, and ultrasonic dispersion treatment is performed at 28 kHz for 5 minutes to prepare the coating sol. In this embodiment, the coating sol is prepared so that the mass ratio of CNF:BTESE is 1:1, but this is not limited thereto, and the mass ratio is preferably in the range of CNF:BTESE = 1:1 to 1:100.
[0028] In addition, in this embodiment, CNF is used as the nanomaterial, but this is not limited to this, and any material that can be directly coated onto the porous support may be used, for example, graphene oxide.
[0029] As described above, the separation layer 11 according to the present embodiment contains organosilica having a silsesquioxane structure, the precursor of which is a crosslinked alkoxysilane such as BTESE, BTESM, BTESP, BTESB, or BTPA, or a side-chain alkoxysilane such as methyltriethoxysilane or aminopropyltrimethoxysilane. This is silicone ((RSiO) n ) is soft, making it difficult to improve the separation properties of the separation membrane, and silica (SiO2) is hard, making the separation layer hard and prone to cracking, and prone to pinholes, among other issues, so silsesquioxane is considered appropriate. However, the organosilica of the separation layer 11 may contain silicone and silica. Metal ions may also be added to the silsesquioxane.
[0030] Further, in this embodiment, hydrochloric acid is dripped onto BTESE, but this is not limited thereto, and hydrochloric acid may be dripped after mixing the BTESE sol and the CNF sol.
[0031] Next, in the coating step, the coating sol prepared in step S13 is applied to the support 12 (step S14). As described above, the support 12 is a porous substrate, and cellulose ester (estimated pore size: 0.1 μm), cellulose (filter paper, estimated pore size: 5 μm), polyacrylonitrile, fluororesin such as polytetrafluoroethylene, polymethylpentene, polysulfone (CF30K manufactured by Nitto Denko Corporation, estimated pore size: 30 nm), etc. can be used.
[0032] Subsequently, as a membrane forming step, a membrane of the coating sol is formed on the support 12 (step S15). More specifically, the support 12 to which the coating sol has been applied in step S14 is filtered under reduced pressure or pressure. The conditions for reduced pressure filtration and pressure filtration are not particularly limited, but for example, the support 12 side is depressurized to 80 kPa for 30 minutes to perform reduced pressure filtration. In addition, in the case of pressure filtration, for example, the separation membrane side (coating sol side) is pressurized to 2 atmospheres to perform pressure filtration.
[0033] After the coating sol is coated on the support 12, the support 12 is heat-treated as a heat treatment step to densify the separation layer 11 (step S16). The heat treatment conditions are, for example, 90°C for 30 minutes. In this embodiment, the separation layer 11 is densified by heat treatment, but the heat treatment may not be performed. However, in order to improve the film formability, it is preferable to heat-treat the coating sol at 50 to 150°C.
[0034] Through the above steps, a thin separation layer 11 can be formed directly on the support 12. That is, the separation membrane 10 can be formed without forming an intermediate layer. Therefore, it is possible to obtain a separation membrane 10 with reduced permeation resistance and high permeability. In addition, by using organosilica having a silsesquioxane structure, a separation layer 11 with adjustable pore size can be formed, so that the selectivity of the separation membrane 10 can be improved.
[0035] (Separation membrane permeability evaluation) To evaluate the permeability of the separation membrane, a saturated water vapor / nitrogen permeation experiment was carried out. The separation conditions were a 25°C environment, a mixed gas was supplied to the separation membrane 10 at 500 ml / min, and the supply pressure of the mixed gas was 100 kPa. Table 1 shows the experimental results of the water vapor permeability, nitrogen permeability, and separation factor of the separation membrane containing CNF in the separation layer and the separation membrane containing CNF and BTESE in the separation layer. [Table 1]
[0036] The transmittance was calculated according to the following formula. P i =M i / (SΔt(P fi -P pi )) M i :Permeated substance amount [mol] S: Membrane area [m 2 ] Δt: Repair time [s] P fi :Upstream partial pressure [Pa] P pi : Downstream partial pressure [Pa]
[0037] The separation factor α is a factor calculated by the following formula, and a larger value indicates higher separation ability. α = (Y W / Y N ) / (X W / X N ) X W : Water molar concentration upstream of the separation membrane X N : Nitrogen molar concentration upstream of the separation membrane Y W : Water molar concentration downstream of the separation membrane Y N : Nitrogen molar concentration downstream of the separation membrane
[0038] As shown in Table 1, separation membrane 10 containing CNF and BTESE has a higher water vapor permeability and separation factor than separation membrane 10 containing CNF in separation layer 11. It is believed that the inclusion of BTESE in separation layer 11 makes it possible to form pores with small diameters, thereby increasing the selectivity of separation membrane 10.
[0039] As described above, the separation membrane 10 according to the present embodiment includes a nanomaterial in the separation layer 11, so that the separation layer can be directly coated on the porous support. This eliminates the permeation resistance due to the intermediate layer, so that the permeability of the separation membrane 10 can be improved. In addition, the separation layer 11 includes organosilica having a silsesquioxane structure, so that the chemical structure of the separation layer 11 can be controlled to adjust the pore size, and the selectivity can be improved. Therefore, the separation membrane 10 according to the present embodiment has high permeability and selectivity, so that separation treatment such as water treatment can be performed more efficiently. In addition, the alkoxysilane, which is a precursor of organosilica having a silsesquioxane network structure that performs separation, and the nanomaterial can be applied to the porous support as a single unit, so that the membrane production process can be simplified.
[0040] (Characteristics of cellulose nanofibers) The heat resistance of the CNF contained in the separation layer 11, which affects the characteristics of the separation membrane 10 according to the present embodiment, was evaluated. CNF M sol (manufactured by Sugino Machine Co., Ltd., concentration 2 wt%, fiber diameter 10 to 50 nm, degree of polymerization 650) was used as the CNF. After the CNF sol sample was held at 100°C for 3 hours in a nitrogen atmosphere and an air atmosphere, it was heated at a rate of 10°C / min and held at 500°C for 4 hours. FIG. 4 shows the results of thermogravimetric analysis (TGA) of the CNF contained in the separation layer 11. As shown in FIG. 4, it can be confirmed that the relative mass decreased at about 300°C in a nitrogen atmosphere and an air atmosphere.
[0041] The CNF sol was heat-treated for 20 minutes at 25°C, 100°C, 200°C, and 300°C, and the structure of the CNF sol was analyzed. Figure 5 shows the measurement results of the structure analysis of the CNF contained in the separation layer 11 by Fourier transform infrared spectroscopy (FT-IR). As shown in Figure 5, the peaks indicating -OH, CH, -OH, and C-OH, which are detected in the CNF sol heat-treated at 25°C, 100°C, and 200°C, are not detected at 300°C.
[0042] The results of structural analysis using thermal gravimetric analysis (TGA) and Fourier transform infrared spectroscopy (FT-IR) indicate that thermal decomposition of the CNF sol occurred at around 300°C, indicating that the heat resistance of the CNF sol is around 300°C. In addition, the presence of hydroxyl groups was confirmed even at high temperatures, indicating the high hydrophilicity of the CNF sol.
[0043] (Permeability evaluation of separation membranes containing CNF in the separation layer) The permeability evaluation of the separation membrane containing CNF in the separation layer 11 was performed under the conditions and calculation method described above. Figure 6(a) shows the separation coefficient versus the thickness of the separation layer 11, and Figure 6(b) shows the water vapor permeability and nitrogen permeability versus the thickness of the separation layer 11.
[0044] As shown in FIG. 6(a), the separation coefficient increased and the separation ability improved with an increase in the thickness of the separation layer 11. Also, as shown in FIG. 6(b), the water vapor permeability of the separation membrane did not change significantly even when the thickness of the separation layer 11 was increased. Also, the nitrogen permeability of the separation membrane was 10 -6 or more, and when it is 10 μm, it is 10 -6 From 10 -8 It is considered that as the thickness of the separation layer 11 increases, the pores through which nitrogen can pass are blocked by the coating of the CNF sol. [Industrial Applicability]
[0045] The present invention is suitable for separation of materials requiring high permeability and selectivity, and is particularly suitable for the removal of water from mixtures of liquids and gases. [Explanation of symbols]
[0046] 10 separation membrane, 11 separation layer, 12 support, 20 separation membrane, 21 separation layer, 22 intermediate layer, 23 support
Claims
1. A porous support having a pore size of 30 nm or more and 5 μm or less; A separation layer formed on the porous support and containing a nanomaterial and an organosilica having a silsesquioxane structure; The nanomaterial comprises: A cellulose nanofiber having a fiber diameter of 1 nm or more and less than 100 nm, or a graphene oxide having a thickness of 1 nm or more and less than 10 nm and a sheet length of 100 nm or more. A separation membrane characterized by:
2. The porous support is a cellulose ester, cellulose, polyacrylonitrile, polytetrafluoroethylene, polymethylpentene or polysulfone; The separation membrane according to claim 1 .
3. The organosilica is produced using an alkoxysilane as a precursor. The separation membrane according to claim 1 or 2.
4. A preparation step of preparing a coating sol containing a nanomaterial and an organosilica having a silsesquioxane structure; A coating step of coating the coating sol onto a porous support having a pore size of 30 nm or more and 5 μm or less; a film-forming step of forming a film by filtering the coating sol applied in the coating step under reduced pressure or pressure; A heat treatment step of heat-treating the coating sol formed in the film-forming step to form a separation layer, The nanomaterial comprises: A cellulose nanofiber having a fiber diameter of 1 nm or more and less than 100 nm, or a graphene oxide having a thickness of 1 nm or more and less than 10 nm and a sheet length of 100 nm or more. A method for producing a separation membrane.
5. The organosilica is produced using an alkoxysilane as a precursor. The method for producing a separation membrane according to claim 4.
6. The porous support is a cellulose ester, cellulose, polyacrylonitrile, polytetrafluoroethylene, polymethylpentene or polysulfone; The method for producing a separation membrane according to claim 4 or 5.
Citation Information
Patent Citations
Low dielectric coefficient polyimide / oligomeric silsesquioxane nano hybrid film and preparation thereof
CN101372534A
Coating composition
JP2004168588A
Composition comprising silsesquioxane and hydroxyalkyl cellulose resin composition comprising silsesquioxane
JP2009035515A
Silicone porous body and method for producing the same
JP2017025275A
Gas separation membrane module
JP2019042636A